Integration of Smart Monitoring Systems in Marine Engineering: A Management Approach to Edge Computing and Sensor Technologies - Umoren, Goodnews E.; Flores, Jelissa G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aimed to investigate how these smart monitoring technologies can be effectively implemented in marine engineering practice through a structured, management-oriented approach. The study utilized a descriptive-correlational approach with the participation of selected 106 marine engineering personnels within the Philippines. The study was focused on human resource and competency development, process optimization, system integration management, and project implementation supervision among maritime companies in the Philippines. The study used various statistical methods to analyze the profile of the respondents and evaluate the identified problems and best practices such as frequencies, percentages, and weighted means. The Pearson Product-Moment Correlation Coefficient (r) was employed to test the relationship existing between the level of difficulty and change in the best practices in the four major areas. The results indicated that the project implementation monitoring was the most difficult with the mean of 3.13, whereas system integration management was the least with the mean of 2.42.  The management’s best practices regarding system integration received the highest score of 3.50, which is significant for the technology’s integration effectiveness. Although the issues of human resource and competency development showed weak and insignificant correlations with the related best practices, several other areas, especially system integration management, process optimization, and project implementation oversight, showed stronger correlations This means that when difficulties arise in these areas, the organization will be more willing to adopt flexible, effective best practices to maintain operational performance and promote the successful adoption of technology in maritime engineering operations.